2022
DOI: 10.17507/tpls.1212.02
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Affective Factors in English Speaking Skills

Abstract: Language learning is a part of the psychological process as it is based on the individual differences of various learners. Speaking skills are classified as the abilities that allow us to speak meaningfully with one another. It provides us with the ability to express information verbally. Affective factors such as self-esteem, self-confidence, anxiety, fear of failure, shyness, motivation, attitude, empathy, and so on influence the development of speaking skills. These affective factors are crucial in second l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…In various studies, oral proficiency in EFL, which has been interrelated with emotions, has shown a specific dependence on positive and negative emotions. For instance, it tends to decline with negative emotions such as anxiety, fear, shyness, and nervousness (Kiruthiga and Christopher, 2022). Previous research by Bassa (2017) also highlighted the impact of negative emotions on oral proficiency in English, irrespective of the linguistic context, reinforcing the idea that emotional barriers are a shared concern among EFL students.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…In various studies, oral proficiency in EFL, which has been interrelated with emotions, has shown a specific dependence on positive and negative emotions. For instance, it tends to decline with negative emotions such as anxiety, fear, shyness, and nervousness (Kiruthiga and Christopher, 2022). Previous research by Bassa (2017) also highlighted the impact of negative emotions on oral proficiency in English, irrespective of the linguistic context, reinforcing the idea that emotional barriers are a shared concern among EFL students.…”
Section: Discussionmentioning
confidence: 87%
“…Oral proficiency is realized through frequent interactions in the classroom, and when these interactions are facilitated with a more influential affective factor in oral proficiency (Kiruthiga and Christopher, 2022) and create an excellent social climate, which, in addition to affecting communication disposition again (Mohammad et al, 2022;Aldosari et al, 2023), can change personal perceptions of self-efficacy through observation and peer feedback, increasing enjoyment (Shao and Parkinson, 2021). Observation and peer feedback in a supportive and respectful environment can increase confidence in oral skills, enjoyment, and students' interest in learning English.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its importance, speaking skills often lack a place in the educational curriculum, requiring sustained effort from both students and educators. Fluency precedes accuracy, underscoring the importance of clear comprehension before perfect speech can be achieved (Kiruthiga & Christopher, 2022).…”
Section: Introductionmentioning
confidence: 99%